The gender perspective in the opinions and discourse of women about caregiving - Inmaculada Lancharro Tavero; Eugenia Gil García; Juana Macías Seda; Rocío Romero Serrano; Isabel María Calvo Cabrera; Almudena Arroyo Rodríguez (Revista da Escola de Enfermagem da USP, 2018)
ABSTRACT Objective: To investigate the meanings given by women caregivers to their care practices and to analyze the relationship between such practices and their work history. Method: This was a phenomenological qualitative cohort study conducted in Seville, Spain, with family caregivers. Data were collected using semi-structured interviews and submitted to content analysis, using Atlas-ti GmbH software version 5.0®. The following categories emerged: caregiving history and work history, and the meaning of care in their lives. Results: Twenty caregivers participated in the study. Women caregivers told stories of wide-ranging care, including several individuals in their family at different moments. They performed different forms of care, encompassing physical and social dimensions. Their discourse expressed the contradiction between their caregiving role and entering and/or maintaining their place in the labor market. Conclusion: The women expressed a concept of comprehensive care that includes responsibility, availability, and companionship, as well as emotional states, which greatly impact health. They tailored their participation in the labor market according to their family’s care needs. Thus, the gender perspective must be incorporated by health care providers who work with the health of caregivers.